UContent : the information professional's guide to user-generated content - Tomaiuolo, Nicholas G. (Information Today, Inc. New JerseyUS, 2012)
Examines the ubiquity of user-generation content, which has been defined at various times as content created and published by the end users online; various kinds of media content, publicly available, that are produced by end users; a website where either the entire content or large portions are contributed by the site users; a realm where users are not only consuming content, but also participate in creating content; and content made publicly available over the Internet which reflects a certain amount of creative effort, and is created outside of professional routines and practices.